THE RELATIONSHIP BETWEEN THE LEVEL OF PARENTAL KNOWLEDGE AND THE INCIDENCE OF DIARRHEA IN CHILDREN UNDER FIVE YEARS OF AGE IN HOSPITAL INPATIENT ROOMS - Katarina Ratnawati; Christina Ririn Widianti; Deni Lusiana (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Diarrheal diseases are still a concern, especially in children's health. The main cause of death in diarrhea is due to dehydration resulting in fluid and electrolyte loss. One of the factors that influence the incidence of diarrhea in children is parental knowledge. The purpose of this study was to determine the relationship between parental knowledge and the incidence of diarrhea in children under five years of age at Santo Antonio Baturaja Hospital, South Sumatra. This study used a cross sectional design, namely the level of parental knowledge (independent variable) to the incidence of diarrhea in toddlers (dependent variable). Sampling in this study using accidental sampling technique using the slovin formula as many as 52 respondents. This study was conducted in the inpatient room of Santo Antonio Baturaja Hospital, South Sumatra. Data collection used a questionnaire of parental knowledge about diarrhea that had been tested for validity and reliability. The results showed that most of the 24 respondents (46.2%) had a good level of knowledge of parents of children under five years of age and most of the 33 respondents (63.5%) had acute diarrhea. The results of statistical analysis using Spearman obtained a p value of 0.0001 and r = 0.455 which means that there is a relationship between parental knowledge and the incidence of diarrhea in children under five years of age at Santo Antonio Baturaja Hospital with moderate correlation strength. Researchers suggest that education for parents about diarrhea in toddlers should be provided so that they can better prevent and manage diarrhea cases.